(untitled) (KIUT Publication, 2025)
According to a study published in the JAMA Internal Medicine journal, middle-aged Britons who consume coffee in moderation have a 10–15% lower risk of mortality. Coffee contains antioxidants that help eliminate free radicals in the body, which combat aging. Coffee antioxidants also help fight cancer, both types of diabetes, and Parkinson’s disease.